Profile of pregnant adolescents with history of domestic violence - Rosana Santos Mota; Mariana Matias Santos; Adriana Diniz Rodrigues; Climene Laura de Camargo; Nadirlene Pereira Gomes; Normélia Maria Freire Diniz (Rev Rene)
This quantitative study aims to evaluate pregnant adolescents in relation to socio demographic, gynecological and obstetric aspects and the experience of domestic violence. The subjects were 34 pregnant adolescents who got prenatal care in the city of São Francisco do Conde (Bahia, Brazil). Interviews were conducted. The majority of pregnant adolescents was between 16 and 19 years old and was single, black, non-educated, and financially dependent on parents or husband/partner, having initiated a sexual relationship before the age of 15. More than 40% declared a history of domestic violence. Some of them revealed the experience of domestic violence during pregnancy. In face of this reality, a professional look is necessary in order to recognize domestic violence as an aggravating factor to the health of these adolescents, a fact which has not been perceived in health care.